A Review of Spectral Methods for Dispersion Characterization of Carbon Nanotubes in Aqueous Suspensions. (28th June 2015) - Njuguna, Jidraph; Vanli, O. Arda; Liang, Richard
Abstract : Characterization is a crucial step in the study of properties of nanomaterials to evaluate their full potential in applications. Carbon nanotube-based materials have properties that are sensitive to size, shape, concentration, and agglomeration state. It is therefore critical to quantitatively characterize these factors in situ, while the processing takes place. Traditional characterization techniques that rely on microscopy are often time consuming and in most cases provide qualitative results. Spectroscopy has been studied as an alternative tool for identifying, characterizing, and studying these materials in situ and in a quantitative way. In this paper, we provide a critical review of the spectroscopy techniques used to explore the surface properties (e.g., dispersion) characteristics of carbon nanotubes in aqueous suspensions during the sonication process.